Efektivitas Media Busy Book Dalam Upaya Meningkatkan Kemampuan Penjumlahan bagi Anak Tunarungu Kelas V di SLB Al- - Fitri Yanti; Grahita Kusumastuti (Universitas Negeri Padang, 2023)
This busy book media is used to determine the effectiveness of busy book media on children's ability to add without saving for deaf children in class V SDLB. This is experimental research form Single Subject Research (SSR) with Multiple Baseline Across Subjects Design. The subjects in this study were deaf children in class V SDLB. Research variables increase the ability to add without saving. Data collection techniques used are tests and data collection tools in the form of test items. Graphical visual analysis is a data analysis technique used in this study. The results of the research and discussion explain that the ability to add without storing in children has increased during the intervention in the form of busy book media. It has been proven that there is an increase in the summation ability from the baseline phase to the intervention phase where the results of the trend of stability mean level A1 in the first subject (K) is 2.75 then there is an increase when given intervention B where the mean level is 5.33 and in the second subject ( Q) the results obtained that the mean level stability trend of A1 was 3.4 then there was an increase when given intervention B where the mean level was 4.7. So it can be concluded that there is an increase in each condition which means the child is able to do addition without saving.